Vaping and COVID-19: Insights for Public Health and Clinical Care from Twitter - Anuja Majmundar (MDPI AG, 2021)
This study describes key topics of discussions on Twitter at the intersection of vaping and COVID-19 and documents public reactions to announcements from authoritative health agencies. Twitter posts containing vaping and COVID-19-related terms were collected from 1 December 2019 to 3 May 2020 (n = 23,103 posts). Text classifiers and unsupervised machine learning were used to identify topics in posts. Predominant topics included COVID-19 Respiratory Health (18.87%), COVID-19 Susceptibility (17.53%), Death (10.07%), Other COVID-19 Health Effects (9.62%), and Severity of COVID-19 (7.72%), among others. Public conversations on topics, such as Severity of COVID-19, Transmission, Susceptibility, Health Effects, Death, and Smoking cessation, were shaped by announcements from U.S. and international health agencies. Armed with the insights from this study, medical providers should be prepared to discuss vaping-related health risks with their patients in the era of COVID-19. Misconceptions around vaping as a protective behavior from, and an effective treatment against, COVID-19 should also be corrected.